Severity grade of complaints from X-ray imaging on the elderlies with knee osteoarthritis - Juwita, Citra Puspa; Damayanti, Rita; Besral; Aras, Djohan; James Manik (International Journal Of Community Medicine And Public Health, 2023)
Background: This study aimed to investigate the correlation between severity of osteoarthritis with disorder or problem experienced by elder osteoarthritis patients. Methods: This was a cross-sectional study conducted in the period of October until December 2022 in one of the regions in the capital of Indonesia. Data was collected through knee X-ray examination according to Kellgren-Lawrence (KL) classification and direct interview on the elderlies with knee arthritis by using Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) questionnaire. Data analysis was performed with Spearman rank. Results: From a total of 102 elderly participants who were diagnosed with knee osteoarthritis, it was found out that on average, as the osteoarthritis grade increased, the pain also increased. The stiffness and functional ability experienced by the participants were not according to the grade of the osteoarthritis. There was a weak correlation between severity with disorder or problem in the elderlies with osteoarthritis (p=0.030, R=0.214). Differences are only found in the severity of pain between grade 2 and grade 4, and in the severity of functional disorder between grade 1 and grade 3. Conclusions: Complaints of osteoarthritis in the elderlies are not specific for each severity grade.